Pengembangan VR Cardboard sebagai Sarana Media Pembelajaran Fisika Berbasis Realitas Virtual - Zakaria, Aminudin; Anggaryani, Mita (IPF: Inovasi Pendidikan Fisika, 2024)
The research is focused on developing VR Cardboard as a tool for accessing physical learning media through virtual reality. Virtual reality-based media has been advancing over the past decade, requiring additional devices for an optimal learning experience. The research included data collection, design, development, validation, and revision. The VR Cardboard design follows the template provided by the open-source Google Cardboard platform, using cardboard cut to a predetermined design. The VR Cardboard received a validation score of 79%, indicating its suitability for use. The validator recommends adjusting the focal distance of the biconvex lens by 45 mm for clearer observation of 3D objects. Additionally, it is recommended that the VR Cardboard be packaged in a container resistant to wetness, fire, and pressure to ensure its longevity.